2013
DOI: 10.1002/j.2161-007x.2013.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping, Body Dissatisfaction, and Bulimic Symptomatology

Abstract: The authors explored the association among body dissatisfaction, religious coping, and bulimic symptomatology. The results suggest that spiritual discontent religious coping was detrimental for the college female participants (N = 398) when considered in relationship to bulimic symptomatology. Implications of the findings for theory refinement, future research, and clinical practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 56 publications
(134 reference statements)
0
23
0
1
Order By: Relevance
“…These findings corresponded well with previous research and theory in the field. The beneficial influence of specific spiritual beliefs upon eating disorder symptoms has been underscored by several studies (Buser & Bernard, ; Forthun et al, ; Marsden et al, ; Wasson & Jackson, ; Watkins et al, ). For example, as noted earlier, individuals who believed that they were close to God/Higher Power during times of stress reported fewer bulimic symptoms (Buser & Bernard, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings corresponded well with previous research and theory in the field. The beneficial influence of specific spiritual beliefs upon eating disorder symptoms has been underscored by several studies (Buser & Bernard, ; Forthun et al, ; Marsden et al, ; Wasson & Jackson, ; Watkins et al, ). For example, as noted earlier, individuals who believed that they were close to God/Higher Power during times of stress reported fewer bulimic symptoms (Buser & Bernard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Forthun et al () studied 876 college women and found that those who ascribed to an internally motivated, mature faith reported fewer eating disorder symptoms. By contrast, individuals who understood God/Higher Power to be distant and unreliable during stressful events reported increased bulimic symptoms (Buser & Bernard, ). In a study of 605 college women, feelings of being punished by God/Higher Power during stressful situations were associated with more symptoms of bulimia (Buser, ).…”
Section: Eating Disorders and Spiritual Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fitchett et al (1999) and Carpenter, Laney, and Mezulis (2012) reported an association between negative religious coping and increased depression but did not find a link between positive religious coping and decreased depression. Moreover, authors studying other unfavorable health outcomes have reported similar trends, wherein negative spiritual/religious coping had stronger associations with outcomes compared to positive spiritual/religious coping (Buser, 2013;Buser & Bernard, 2013).…”
Section: Spiritual/religious Coping and Depressionmentioning
confidence: 80%
“…We deemed these changes important in order to (a) increase the inclusivity of the survey instrument such that individuals who did not identify with the term ''God'' were not excluded and (b) to ascertain that we were assessing a coping response to a specific type of stress. In addition, we followed the precedent of prior researchers who altered the language of the RCOPE to read ''God/Higher Power''(e.g., Buser, 2013;Buser & Bernard, 2013) and discussions of the importance of measuring an individual's response to a particular stressor versus stress in general (Folkman & Lazarus, 1980). However, these changes may have compromised the psychometric properties of the RCOPE.…”
Section: Strengths and Limitationsmentioning
confidence: 99%